2020
DOI: 10.1159/000507355
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism and Nutritional Status in Hospitalized Patients with Chronic Heart Failure

Abstract: Introduction: Malnutrition is a factor that defines vital prognosis in chronic heart failure. Objective: This study investigated nutritional and metabolic disorders in patients with heart failure by examining the association of severity of heart failure with inflammatory cytokines, appetite-regulating hormones, and energy metabolism. Methods: Subjects were 50 patients with heart failure. On admission, nutritional status was assessed, and biochemical blood tests were performed, including for serum tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…These data corroborate previously published results [3,4,6]. Yasuhara et al [5] concluded in their study that body fat percentage (in BIA) might be a good predictor of energy metabolism and prognosis in CHF patients. Multifactorial analysis by Thomas et al [11] found that a higher body fat mass index (BFMI = FM / body surface area) determined using BIA was an independent prognostic factor of five-year survival in CHF patients (an 11% decrease in mortality risk for every 1 kg/m 2 increase in BFMI), and the combination of low BFMI and lean body mass index increased the risk of all-cause mortality in CHF patients by nearly five times.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data corroborate previously published results [3,4,6]. Yasuhara et al [5] concluded in their study that body fat percentage (in BIA) might be a good predictor of energy metabolism and prognosis in CHF patients. Multifactorial analysis by Thomas et al [11] found that a higher body fat mass index (BFMI = FM / body surface area) determined using BIA was an independent prognostic factor of five-year survival in CHF patients (an 11% decrease in mortality risk for every 1 kg/m 2 increase in BFMI), and the combination of low BFMI and lean body mass index increased the risk of all-cause mortality in CHF patients by nearly five times.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is very important to recognize all the factors that may potentially affect the course of CHF, in order to prevent its exacerbation and reduce the need for hospitalization [1,2]. One of multiple such factors seems to be patients' nutritional status [1][2][3][4][5][6], and especially that the provision of nutritional support can improve the outcomes of patients with CHF [7]. In CHF patients, assessing nutritional status on the basis of anthropometric parameters is not reliable, i.a.…”
Section: Introductionmentioning
confidence: 99%
“…However, IL-6 appeared not to be associated with REE in our cohort, as has been reported in patients with HF. 27 We consider that a relatively lower IL-6 level (median, 4.0 pg/mL; range, 2.4-9.5 pg/mL) in our cohort, compared with patients with lung cancer 15 and in ammatory-bowel disease, 53 represents a stable clinical state, which may mask a potential relationship between IL-6 and REE.…”
Section: Discussionmentioning
confidence: 86%
“…33 A positive association between REE and leptin was observed in cross-sectional studies involving 40 to 50 patients with chronic obstructive pulmonary disease (COPD) 17 or heart failure (HF). 27 Leptin administration in obese or normal participants increased energy expenditure and food intake. Conversely, leptin receptor antagonists reduced REE in patients with lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation